Kroppens mening: Materialitet, repræsentation og penge i La Peau de Chagrin, À rebours og Le Jardin des supplices - Gammelgaard, Signe (Tidskrift för litteraturvetenskap, 2023)
“Embodied Meaning. Materiality, Representation and Money in La Peau de Chagrin, À rebours and Le Jardin des supplices” This article presents readings of three French novels from the nineteenth century, namely Balzac's La Peau de chagrin, Huysmans' À rebours and Octave Mirbeau's Le Jardin des supplices. It examines issues of representation and meaning in relation to debt narratives and the use of bodies as a motif in relation to debt, and it argues that, in these novels, literary language and monetary representation displays parallel developments, exemplified through the shift from realist aesthetics to decadent literary style. The article ends by connecting a shifting representative function and related issues of meaning, to modern tendencies in literature, and the function of the human body in these narratives.